Monoecocestus parcitesticulatus Rego, 1960 (Anoplocephalidae) a new cestode in Peru - Naupay, Asucena (1974)
In 1970 Tió and Guerrero studied parasites of Cavia aperea Erxl from Canchis and Canas in Cuzco, Peru, they found that 28% of C. aperea were parasitized with Monoecocestus sp. cestodo Anoplocephalideo.